Analisis Pola Konsumsi Air Menggunakan Algoritma Random Forest Classifier Pada Distribusi Air Bersih Desa Rempoah Baturraden - Ngarifatul Khofiyah, Salma; Hamdi, Aulia; Nur Isnaini, Khairunnisak (Jurnal Algoritma, 2025)
Clean water is a basic necessity for communities that must be managed efficiently to ensure its distribution remains equitable and sustainable. In Rempoah Village, water usage is still recorded manually, making it difficult to analyze consumption patterns and detect irregular usage. This study aims to analyze water consumption patterns using the Random Forest Classifier algorithm as an effort to support clean water distribution management by the Berkah Maju Bersama Village-Owned Enterprise (BUMDes). The research data was obtained through observation and interviews with the management, followed by a data preprocessing stage that included data cleaning, missing value handling, data exploration, label encoding, and data division into training and test data. The Random Forest model was used to classify water consumption patterns into three categories, namely economical, normal, and wasteful. The results showed that the model was able to classify the data with an accuracy rate of 100%, where all test data was correctly identified. Based on the analysis results, most customers were in the wasteful category at 56.2%, indicating the need for an evaluation of the efficiency of household water use. These findings prove that the application of machine learning methods can be an effective solution in supporting decision-making and clean water management at the village level in a sustainable manner.